2017
DOI: 10.22159/ijpps.2017v9i6.18522
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Carbon Nanotubes in Nanobiomedicines

Abstract: CNTs is a fullerene molecule, described in 1991 by the Japanese Scientist ‘‘Sumio Iijima’’ as tube-shaped of graphitic carbon, can be obtained either single or multi-walled nanotube, having a diameter measuring on the nanometer scale, and generally known as buckytubes. Carbon nanotubes (CNTs) have established much recent interest as new entities for experimental disease diagnosis and treatment because of their unique electronic, mechanical, thermal, spectroscopic, metallic, semiconducting and superconducting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 124 publications
(143 reference statements)
0
4
0
1
Order By: Relevance
“…Moreover, it can be easily tailored into zerodimensional (0D) fullerenes [60], and one-dimensional (1D) carbon nanotubes (CNTs) [61]. A plentiful literature survey suggested that numerous synthesis methods have been proposed and developed including micromechanical stripping [62], chemical vapor deposition (CVD) [63], and SiC epitaxial growth method, etc Because of graphene's vast plane conjugate structure, electrons exhibit a strong delocalisation impact [64]. Consequently, graphene possesses a zero-band distance, which is characteristic of half-metallic compounds.…”
Section: Graphene Quantum Dots (Gqds)mentioning
confidence: 99%
“…Moreover, it can be easily tailored into zerodimensional (0D) fullerenes [60], and one-dimensional (1D) carbon nanotubes (CNTs) [61]. A plentiful literature survey suggested that numerous synthesis methods have been proposed and developed including micromechanical stripping [62], chemical vapor deposition (CVD) [63], and SiC epitaxial growth method, etc Because of graphene's vast plane conjugate structure, electrons exhibit a strong delocalisation impact [64]. Consequently, graphene possesses a zero-band distance, which is characteristic of half-metallic compounds.…”
Section: Graphene Quantum Dots (Gqds)mentioning
confidence: 99%
“…Materiały te odznaczają się około 100-krotnie większą wytrzymałością na rozciąganie niż stal. Nanorurki charakteryzują się również bardzo dobrą odpornością na działanie podwyższonej temperatury, sięgającej nawet 2800°C, oraz są bardzo dobrymi przewodnikami ciepła (Iijima, 2002;Szadkowski i Pingot, 2016;Sahu et al, 2017). Do badań laboratoryjnych użyto nanorurek wielowarstwowych o średnicy zewnętrznej 10-20 nm, średnicy wewnętrznej 5-10 nm oraz długości 10-30 µm; • tlenek grafenu -utleniona forma grafenu, wytworzona w procesie oksydacji kryształów grafitu z mieszanką kwasu siarkowego, azotanu sodu i nadmanganianu potasu (metodą Hummersa).…”
Section: Charakterystyka Materiałów Zastosowanych Do Badańunclassified
“…The coordination behaviour of hydrazones has been well studied and depends on the pH medium, nature of the substituents and also on the position of hydrazone group relative to other moieties. As biologically active compound [7,8] hydrazone find a remarkable application to cure tumor [9], cytotoxic [10], antiproliferative, antibacterial, antiviral, antifungal [11][12][13][14], tuberculosis, leprosy, along with some mental diseases [15][16][17]. Hence many important enzymatic reactions catalyzed by the transition metal complexes take place only due to presence of Schiff bases [18,19].…”
Section: Introductionmentioning
confidence: 99%